Abundance, diversity, and composition of root-associated microbial communities varied with tall fescue cultivars under water deficit - Hu, Jialin; Miller, Grady; Shi, Wei (Frontiers in Microbiology, 2023)
The plant breeding program has developed many cultivars of tall fescue (Festuca arundinacea) with low maintenance and stress tolerance. While the root-associated microbial community helps confer stress tolerance in the host plant, it is still largely unknown how stress-tolerant cultivars recruit and shape their own microbiota. The study aimed to characterize drought-responsive bacteria and fungi in the roots and rhizosphere of different tall fescue cultivars. Intact grass-soil cores were collected from six cultivars grown in a field trial under no-irrigation for three years. Tall fescue under irrigation was also sampled from an adjacent area as the contrast. Bacterial and fungal communities in roots, rhizosphere, and bulk soil were examined for abundance, diversity, and composition using quantitative-PCR and high-throughput amplicon sequencing of 16S rRNA gene and ITS regions, respectively. Differences in microbial community composition and structure between non-irrigated and irrigated samples were statistically significant in all three microhabitats. No-irrigation enriched Actinobacteria in all three microhabitats, but mainly enriched Basidiomycota in the root endosphere and only Glomeromycota in bulk soil. Tall fescue cultivars slightly yet significantly modified endophytic microbial communities. Cultivars showing better adaptability to drought encompassed more relatively abundant Actinobacteria, Basidiomycota, or Glomeromycota in roots and the rhizosphere. PICRUSt2-based predictions revealed that the relative abundance of functional genes in roots related to phytohormones, antioxidant enzymes, and nutrient acquisition was enhanced under no-irrigation. Significant associations between Streptomyces and putative drought-ameliorating genes underscore possible mechanics for microbes to confer tall fescue with water stress tolerance. This work sheds important insight into the potential use of endophytic microbes for screening drought-adaptive genotypes and cultivars.